Varenicline for smoking cessation: efficacy, safety, and treatment recommendations - Jon O Ebbert; Kirk D Wyatt; J Taylor Hays; et al (Patient Preference and Adherence, 2010)
Jon O Ebbert, Kirk D Wyatt, J Taylor Hays, Eric W Klee, Richard D HurtMayo Clinic College of Medicine, Rochester, MN, USAAbstract: Smoking is the leading preventable cause of morbidity and mortality in the US, and decreasing smoking prevalence is a public health priority. Patients achieve the greatest success when quit attempts involve behavioral therapy combined with pharmacotherapy. Varenicline is the most recent addition to the pharmacotherapeutic armamentarium for the treatment of tobacco dependence. Varenicline is efficacious and cost-effective. Smoking relapse and adverse treatment-related side effects may decrease medication adherence and patient satisfaction with varenicline. In the clinical setting, varenicline treatment can be optimized by reducing doses in patients who experience intolerable side effects, increasing the dose in partial responders, and providing long-term maintenance therapy for relapse prevention.Keywords: varenicline, tobacco dependence, smoking cessation, nicotine addiction